Manajemen Kegiatan Ekstrakurikuler dalam Meningkatkan Prestasi Non Akademik di SMA Sabiluth Thoyyib Pasuruan - Nafi’atul Ilmiyah; Sigit Priyo Sembodo; Ashari Ashari (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research use desciptive qualitative approach. The data was collected by means of interviews, observation and documentation. The data analysis process is carried out starting from data collection, and checking the validity of the data. To check the validity of the research data using the data triangulation method. The results of the study indicate that: 1) Management planning for extracurricular activities in improving non-academic achievement at Sabiluth Thoyyib High School there are 3 activities, namely meetings with stakeholders, extra coordinators and extracurricular coaches, the second is selection for students who participate in extra activities and the last is all students must follow the mandatory extra i.e. scouts. 2) The implementation is held, every Saturday, either extra mandatory or extra optional. 3) The evaluation consists of 2 activities, the first with an assessment of each extracurricular once a month, every mid-semester and one semester. The second is an evaluation meeting from the school with extra supervisors and extra coordinators which is held every mid-semester, semester and yearly.